Dephosphorylation of tuberous sclerosis complex 2 by serine/threonine protein phosphatase 5 - Malanchuk, O.M.; Palchevskyy, S.S.; Filonenko, V.V. (Біополімери і клітина, 2008)
We report here for the first time specific interaction between tuberous sclerosis complex 2 (TSC2) and protein phosphatase 5 (PP5) in mammalian cells. We found that the interaction is stronger in exponentially growing and serum stimulated cells when compared to serum starved cells. In addition, we provide the evidence that PP5 dephosphorylates specifically TSC2 at sites, associated with its activation via AMP kinase (AMPK) pathway. Taken together, these results suggest that PP5 exerts negative regulation on TSC1/2 function through dephosphorylation of AMPK-mediated sites.